Utilizing Social Media as a Digital Education Tool in Higher Education Environments: Pemanfaatan Media Sosial sebagai Sarana Edukasi Digital di Lingkungan Perguruan Tinggi - Irmawati Sagala; Dzulkifli Rahmat Hidayat; M. Armando Farshal Mz; Mutiara Sandrinabila; Nadella Putri; Siti Soleha (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
This community service was carried out to increase students' awareness and concern for the environment at UIN STS Jambi. Based on initial identification, it was found that students' awareness regarding environmental management and environmentally friendly behavior was still lacking, as indicated by the low level of awareness about waste management and the high incidence of smoking behavior on campus. As a service initiative, the team conducted digital education activities by creating educational media such as videos, flyers, and documentary films, which were disseminated through social media platforms such as WhatsApp, Instagram, and YouTube. The main theme of this activity was to raise awareness about the importance of waste management, energy conservation, and environmentally conscious behavior. The students' responses were quite positive, marked by their enthusiasm as seen in the number of posts and positive reactions to the content they shared on social media, particularly on Instagram. Although no formal statistical measurement has been conducted, the participation and responses indicate students’ interest and attention to environmental issues presented through digital media.